Ensuring accessibility of electronic information resources for visually impaired people. Issue 2 (10th June 2014) - Andreas Kleynhans, Stefanus; Fourie, Ina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper addresses the importance of clarifying terminology such as visually impaired and related terms before embarking on accessibility studies of electronic information resources in library contexts. Apart from briefly defining accessibility, the paper attempts to address the lack of in-depth definitions of terms such as visually impaired, blind, partially sighted, etc. that has been noted in the literature indexed by two major Library and Information Science (LIS) databases. The purpose of this paper is to offer a basis for selecting participants in studies of accessibility of electronic information resources in library contexts and to put discussions of such studies in context. Design/methodology/approach – Clarification of concepts concerning visual impairment following a literature survey based on searching two major databases in LIS. To put the discussion in context accessibility is also briefly defined. Findings – Although visually impaired and a variety of related terms such as blind, partially sighted, visually disabled, etc. are used in the LIS literature, hardly any attempt is made to define these terms in depth. This can be a serious limitation in web and electronic accessibility evaluations and the selection of participants. Practical implications – Clearly distinguishing between categories of visually impaired people and the ability of sight of participants is important when selecting participants for studies on accessibility for visually impaired people, e.g. the accessibility evaluation of web sites, digital libraries and other electronic information resources. Originality/value – The paper can make a contribution to the clarification of terminology essential for the selection of participants in accessibility studies, as well as enriching the literature on accessibility for visually impaired people in the context of LIS.